Sociodemographic and disease-related determinants of return to work among women with breast cancer: a German longitudinal cohort study - Christian Heuser; Sarah Halbach; Christoph Kowalski; Anna Enders; Holger Pfaff; Nicole Ernstmann (BMC, 2018)
Abstract Background Return to work (RTW) is a key parameter of outcome quality that ensures social participation. Therefore, this study analyses the sociodemographic and disease-related determinants of RTW among newly diagnosed breast cancer patients. Methods In a prospective, multicentre cohort study, breast cancer patients were surveyed three times: directly after surgery, after 10 weeks, and after 40 weeks. Logistic regression analysis was applied to estimate the association of RTW at 40 weeks following discharge with sociodemographic and disease-related characteristics (n = 577). Results The sociodemographic variables "entrance certificate at a university of applied science" compared to "university entrance certificate" (OR = 3.1, 95%-CI = 1.2-8.1), age group "55-59 years" compared to "18-44 years" (OR = 3.2, 95%-CI = 1.2-8.4) and "having children" (OR = 2.8, 95%-CI = 1.2-6.2) as well as the disease-related variables "rehabilitation" (OR = 0.5, 95%-CI = 0.3-0.9), self-rated health "good" and "excellent" compared to "bad" (OR = 2.7, 95%-CI = 1.4-5.5; OR = 11.6, 95%-CI = 4.2-31.8) and the UICC-classification "stage II" and "stage III/IV" in comparison to "stage 0/I" (OR = 0.5, 95%-CI = 0.3-0.8; OR = 0.2, 95%-CI = 0.1-0.5) significantly affect RTW among breast cancer patients (Nagelkerke's Pseudo-R2 = 0.275). Conclusions The findings show that significant differences in RTW exist between patient groups and suggest that RTW issues must be addressed more effectively before, during and after treatment. For future research on RTW in Germany, longitudinal studies with a follow-up of several years are necessary. Information and support deficits should be tackled by social services or breast care nurses. Trial registration Database Health Services Research, VfD_PIAT_12_001630, registered 01.03.2012